Peran Orang Tua Dalam Mencegah dan Mengatasi Penyimpangan Perilaku Remaja di Kampung Plemahan Surabaya - Yakiya Al Rizkiya Jaya; Dwi Retnani Srinarwati (Universitas Mathla'ul Anwar Banten, 2022)
This research is based on normal social life adolescents should behave in accordance with existing norms, but the facts show that there are deviations in behavior that occur in society. Deviant behavior is the result of an unfinished socialization process. This can be overcome if the role of parents works well. The purpose of this study 1) was to find out how the occurrence of Adolescent Behavioral Deviations in Plemahan Village, 2) the Role of Parents in Preventing Adolescent Behavioral Deviations, 3) the Role of Parents in Overcoming Adolescent Behavioral Deviations. The research method uses a qualitative research approach. There are three data collection techniques used in this study, namely: observation, interviews, and documentation. The results showed that the role of parents in preventing and overcoming behavioral deviations in Kampung Plemahan was through two-way communication, giving love, directing positive activities, and providing an understanding of religious moral values.